EFL students’ perceptions of AI-assisted writing tools: A systematic narrative hybrid review - Tolga Sarıca; Selma Deneme Gençoğlu (Literacy Trek)
This study explores EFL students' perceptions of AI-assisted writing tools through a systematic narrative hybrid review of 19 open-access studies published between 2020 and 2025 by employing a structured selection process presented via a PRISMA flow chart. As AI tools like ChatGPT, Grammarly, and Turnitin become more prevalent, understanding their impact on students' writing skills, self-directed learning, and academic integrity is essential. Data were collected from ERIC, ULAKBİM, Google Scholar, and ResearchGate, using a multi-stage search. Using SWOT and descriptive content analysis, the study examines AI tools' benefits, challenges, and pedagogical implications in EFL writing. Findings suggest that AI improves efficiency, accuracy, idea generation, and personalized learning, yet concerns include over-reliance, plagiarism risks, and ethical issues. By addressing these factors, the study suggests the need for best practices in AI integration into ELT curricula. It emphasizes the need for teacher training, AI literacy programs, and ethical guidelines to ensure responsible AI use while maximizing its benefits.